PENGARUH CITRA MEREK DAN NILAI YANG DIRASAKAN TERHADAP NIAT BELI YANG DIMEDIASI OLEH KEPERCAYAAN PADA PENGGUNA LAYANAN PEMESANAN HOTEL ONLINE DI KOTA BANDA ACEH - Sayid Muhammad Khalis; Halimatussakdiah Halimatussakdiah (Departemen Manajemen, 2020)
Abstract: This study aims to measure the effect of brand image and perceived value on purchase intentions mediated by trust in online hotel booking service users in Banda Aceh City. The population in this study were all users of online hotel booking services in Banda Aceh City. The sample is chosen by multiplying the number of indicators by the numbers 5 to 10. In this study there were 17 indicators of all the variables to be tested. Therefore, the sample that must be used in this study must range from 85 to 170 samples. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involved. Based on the results of HLM analysis, it indicates that brand image influences trust, perceived value influences trust, brand image does not influence purchase intention, perceived value influences purchase intention, trust influences purchase intention, trust mediates the influence of brand image on purchase intention and trust mediate the effect of perceived value on purchase intentions on users of online hotel booking services in Banda Aceh City. Keywords: Brand image, perceived value, trust, purchase intention A